MD-2-LIKE PROTEINS IN CRUSTACEANS: STRUCTURE, IMMUNE FUNCTIONS, AND AQUACULTURE APPLICATIONS - Abubakar Saadu; Emmanuel Ofori-Amponsah (Agency for Marine and Fisheries Extension and Human Resources, 2026)
MD-2-like proteins belong to the MD-2-related lipid-recognition family and function as lipid-binding molecules in innate immunity. In crustaceans, these proteins have been reported to bind lipopolysaccharides and are implicated in antibacterial immune responses, despite the abshence of a canonical TLR4 signaling pathway, though their precise in vivo mechanisms remain unresolved. Homologs identified in shrimp and crabs share conserved structural motifs linked to lipid binding and immune recognition. Evidence from transcriptomics, ligand-binding assays, and functional perturbation studies supports their involvement in antibacterial defense, although in vivo mechanisms remain unresolved. This narrative review synthesizes current knowledge on MD-2-like proteins of the ML (MD-2-related lipid-recognition) superfamily in crustaceans, focusing on their structure, distribution, and putative immune functions. Clarifying the biological roles of these proteins may in the future inform immune-based approaches to disease management in crustacean aquaculture, pending functional validation in vivo.